Trichobezoar: a rare clinical rendezvous with twin sisters - Almuawi, Abdulrahman; Alsamahy, Omar; Fahiem-Ul-Hassan, Mir; Abdelhamid, Brahemi (International Surgery Journal, 2020)
Trichobezoar is very uncommon in the pediatric age group. Till now no familial predisposition has been reported. We hereby report our clinical experience with eight years old twin sisters one of whom had a huge gastric trichobezoar and other one had a history of trichotillomania with recurrent vomiting and weight loss. An eight years old female child, one of the twin, presented with history of recurrent vomiting. Abdominal examination revealed firm mass in epigastric region. X-ray abdomen showed the transverse colon pushed down. Ultrasonography revealed echogenic mass in the stomach. Preoperative diagnosis of trichobezoar was achieved by a computed tomography (CT) scan. Laparotomy was done through the midline abdominal incision after initial session of resuscitation. A huge mass of hair was retrieved from the stomach part of which was passing into the duodenum. Patient was found to have underlying trichotillomania and obsessive compulsive disorder. As the patient was one of the twins, other sibling was called and evaluated for the mental health. Interestingly, she was found to have trichotillomania and trichophagia. Examination revealed sparse scalp hair. X-ray and the sonography of the abdomen were normal. Patient was advised endoscopic examination which the guardian of the patient refused. Patient was put on outpatient department (OPD) follow up after psychiatric counselling. Trichobezoar should be suspected in a pediatric patient of gastrointestinal symptoms, epigastric mass and anemia with history of trichophagia. Open surgery gives optimum results. Sibling of an affected twin must be evaluated on the similar lines and managed accordingly.